Community Engagement to End Child Early Forced Marriage – Experiences in Selected South Asian Countries - Frances J. Ferreira (Commonwealth of Learning, 2017)
Sustainable Development Goal (SDG) 5, “achieve gender equality and empower all women and girls”, emphasises the need for “providing women and girls with equal access to education, health care, decent work, and representation in political and economic decision-making processes [which] will fuel sustainable economies and benefit societies and humanity at large” (UN, 2015). Millions of girls are forced into early marriage for economic and cultural reasons and denied the opportunity for education. Within the context of sustainable development, it is critical to raise awareness among communities that child marriage has wide ranging negative consequences for development and that allowing girls to have education and training can add enormous value to their society as well as their personal and family lives. This study aims to identify the role of community engagement and local community organisations in contributing towards ending child, early and forced marriage (CEFM) through ensuring equitable access of marginalised and out-of-school girls to education and training. The study was based on data collected from surveys that had been administered to 755 out-of-school girls, affected by CEFM in both urban and rural areas of three selected South Asian Association for Regional Co-operation (SAARC) countries, that is, Bangladesh, Pakistan, and India.